RADIOLOGICAL BIOMARKERS ON THE CONE BEAM COMPUTED TOMOGRAPHY BASIS FOR THE FUNCTIONAL ASYMMETRY DETECTION OF THE MAXILLA AND MANDIBULA IN YOUNG PEOPLE - Kukhlevskyi Yu.І.; Masna, Z.Z. (World of Medicine and Biology, 2018)
Cone beam computed tomography (CBCT) is used o determine the 3D and cross-sectional images, as well as the quality of craniofacial bone structures through the resolve of bone dentistry, based on gray scales Hounsfield Units values of the obtained images. The purpose of the study was to examine the dimensions (width, length, and height) and bone dentistry of the maxillar (MLs) and mandibular segments (MDs) and their correlations with age and sex and to identify different anatomical types functional asymmetry of mandible in young men and women. The observation group comprised 120 persons (45 men and 75 women) without diseases in their history which could affect the bone tissue condition. Taking into account the exclusion criteria, the working group included 40 persons, 21 men and 19 women. All the examined were subdivided into two age-related groups: 1st 21-28 years; 2nd – 29-35 years. The 3 dimensions 3D of all 400 MDs were measured on cone beam computed tomography (CBCT). The dimensions (width, length, and height) of every segment vary according to patient age and sex. The MLs and MDs dimensions conform to particular anatomical types, which should be taken into account, as anatomical functional asymmetry when dental treatment applied. It was also found that the thickness of the upper jaw collar and the cellular part of the mandible in women was 20% lower than that of men. While studying the ratio of the bone tissue layers thickness to the jaw cell sections at the level of the corresponding segments in women of both groups, it was established that the maximum thickness of the spongy layer is preserved in 100% of the examined jaws in the segments of the large molar teeth of the mandible. It was found that the thickness of the compact oral plate was greater than that of the compact vestibular plate, which was of the highest importance in women of 29-35 years of age at the level of segments 31-41 of the mandible. A similar trend was observed during the study of a compact oral plate. Also, in persons of the first group of 22-28 years of age, it was found that the largest thickness of the spongy layer is in the segments of the jaw incisors, whereas in women of 29-35 years the most significant changes were in the upper jaw collar, indicating signs of asymmetry, which is important to take into account for implementation of dental therapeutic manipulations. In women of the second age group, the maximum thickness of the compact plate was at the oral level in segments 31-41 of the mandible compared with the vestibular data. The minimum thickness of bone tissue remains in a compact vestibular plate in the upper jaw in segments 11-21. CBCT could be the helpful tool for evaluation radiological biomarkers of the early signs of bone thickness and bone density and creation preventive personalized medical strategy. The present analyses suggest that an adentia may be the risk factor for the early signs of bone density in asymptomatic young individuals.